Perbandingan Parameter Hidraulik Perencanaan Bendung Gerak Kantelstuw Dengan Bendung Tetap Di Bendung Doorbraak, Almelo, Belanda - Chairevita Novia Mediana; S. Kamilia A.; Rizki Robbi R. Alam; Dwi Indriyani; Bagas Yoga P; Made Indrayana S; M Fadhlan Rosyidi (Jurnal Aplikasi Teknik Sipil, 2025)
The Doorbraak Weir is located in the De Doorbraak Diversion, channeling water from the Loolee River to the Eksosche Aa River. This weir is a fixed cascade type with a height of 2.1 m, serving flood control as well as livestock and agricultural needs. The required water level is +10.5 NAP, but this is often not met during the summer because the weir crest elevation is only +10.3 NAP. To address this, a plan is proposed to convert the weir into a movable kantelstuw or tilting gate. The proposed gate has a crest elevation of +10.5 NAP, with dimensions of 0.5 m x 1.5 m and a gate base height of 0.8 m. Analysis shows that the movable weir is safer, with a Froude number of 2.5 and a jump length of 1.92 m, compared to the fixed weir. The gate operation scenario meets the minimum freeboard requirement of 0.90 m, and the levee is proven to be safe from backflow. Based on hydraulic parameter comparisons, the movable kantelstuw type weir is recommended for the Doorbraak Weir construction.